MENTAL HEALTH CARE: AN INTEGRAL PART OF DISASTER MANAGEMENT: Mental Health Care - Rana, Mowadat Hussain; Ali, Sohail (Pakistan Armed Forces Medical Journal, 2018)
Disasters, whether man made or natural, are complex events having the capacity to disrupt normal functioning of a society, change people’s lives and challenge the coping abilities of individuals and society [1].Disaster management is a highly specialized and an evolving field of our times. With the world becoming more vulnerable to conflicts, wars and acts of terrorism, the concomitant happenings of natural calamities further increase the susceptibility of humankind. The new ‘disease’ called disaster needs to be evaluated, profiled and managed effectively using a comprehensive and an all-encompassing approach in order to make mankind survive.The disasters are divided into man-made and natural. It is estimated that the world has seen around 11 extreme earthquakes which changed the structure of the earth [2]. The world is hit by 220 natural catastrophes, 70 technological disasters and three armed conflicts every year. On the average there are 2-3 disasters in their emergency phase, 15-20 in their recovery phase and about 12 conflict based emergencies in progress [3]. Although human body is not physiologically designed to handle disasters, the contemporary man has to find ways to face this new challenge.No nation can be prepared enough for facing such unpredictable forces. Experience with disasters has revealed that whereas destructive force of the calamity is important in determining the trauma it can produce, the vulnerability of the population it afflicts is equally important [3]. Whereas the disasters cannot be predicted, the susceptibility of the people can be improved by devising effective preparedness and planning to combat the aftermath of disasters.This planning includes pre-emptive appreciation of the nature of disasters and the factors operating in the particular population in which it occurs. It is however important to guard against a blind following of a plan developed in the West or in response to another calamity elsewhere. Such an approach would not only reflect insensitivity to local needs and cultural variations but would also be an unscientific quick-fix remedy. Yet the experience gained in the management of a disaster in one part of the world can be a useful starting point.